Nilai-Nilai kepemimpinan Khadijah binti Khuwailid dalam Pembentukan Karakter Perempuan pada Pendidikan Dasar - Lathifah; Hindun Lubis; Ica Habibatul Barokah; Rossalita; Mustika Sari'ah Siagian (Jurnal Prasasti Ilmu, 2026)
This study aims to analyze the leadership values demonstrated by Khadijah bint Khuwaylid and explain their actualization in building female character in primary education. This study employed a qualitative research method using a library research approach. Data were collected from books, scientific journals, articles, and previous studies related to women’s leadership, character education, and Islamic educational values. The collected data were analyzed using content analysis techniques. The findings indicate that Khadijah bint Khuwaylid demonstrated leadership values including independence, responsibility, confidence, empathy, and social awareness. These values remain relevant to contemporary character education and may be actualized through value-based learning activities, positive role models, supportive school environments, and collaboration between schools and families. Therefore, Khadijah's leadership values can serve as an inspirational framework for strengthening female character development in primary education.